2008
DOI: 10.1080/10715760802510069
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress early in pregnancy and pregnancy outcome

Abstract: The objectives of this study were to determine whether oxidative stress early in pregnancy influenced pregnancy outcome. A combination of assays were used for exogenous and endogenous anti-oxidants together with two well accepted biomarkers for oxidative stress, the urinary excretion of 8-iso-PGF(2alpha) (a biomarker marker for lipid oxidation, n=508) and 8-oxo-7,8 dihydro-2 deoxyguanosine (8-OHdG, a biomarker for DNA oxidation, n=487). The two biomarkers tracked different pregnancy outcomes. Isoprostanes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 41 publications
4
71
2
1
Order By: Relevance
“…22 Another study (N=503) measured 8-isoprostane in maternal plasma collected once between 24–26 weeks gestation and observed higher levels in mothers who developed preeclampsia or had small for gestational age infants. 20 Neither group observed an association with PTB, though the number of cases in each study was small (N=48 and 37, respectively).…”
Section: Commentmentioning
confidence: 99%
“…22 Another study (N=503) measured 8-isoprostane in maternal plasma collected once between 24–26 weeks gestation and observed higher levels in mothers who developed preeclampsia or had small for gestational age infants. 20 Neither group observed an association with PTB, though the number of cases in each study was small (N=48 and 37, respectively).…”
Section: Commentmentioning
confidence: 99%
“…Increased oxidative stress in human pregnancy has also been implicated in the pathogenesis of preeclampsia [14-15], preterm birth [16], intrauterine growth retardation [14, 17] and low birth weight deliveries [18]. Stein et al [16] recently reported that elevated urine 8-OHdG concentrations measured in early pregnancy were associated with reduced infant birthweight and with shortened length of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Stein et al [16] recently reported that elevated urine 8-OHdG concentrations measured in early pregnancy were associated with reduced infant birthweight and with shortened length of gestation. To our knowledge, no previous study has examined the extent to which, if at all, maternal urinary 8-OHdG in early pregnancy may be related with incident gestational diabetes mellitus (GDM).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high levels of 8-OHdG in placental DNA or urine from pre-eclamptic women have been reported, although other studies have described no significant change [Takagi et al 2004;Hung et al 2010;Peter Stein et al 2008]. In our current study, we examined the levels of 8-OHdG in pre-eclamptic placental tissue in the context of IDO expression to further evaluate the significance of the antioxidant function of IDO in this disorder.…”
Section: Introductionmentioning
confidence: 99%